Let's pick apples! - Depken, Kristen L; Dynamo Limited; Penguin Random House; Random House Children's Books (New York Random House, 2017)
Barbie and her sisters spend a fall day picking apples
At head of title: Barbie
English Stories
Preschool-Kindergarten
Keywords: Barbie -- (Fictitious character) -- Juvenile fiction; Barbie -- (Fictitious character) -- Fiction; Barbie -- (Fictitious character); Apples -- Juvenile fiction; Picture books; Sisters -- Juvenile fiction; Apples -- Fiction; Sisters -- Fiction; JUVENILE FICTION / Media Tie-In; Apples; JUVENILE FICTION / Media Tie-In; Picture books; Sisters; Readers (Publications.); Fiction; Juvenile works